1995
DOI: 10.1007/bf00124080
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of somatic embryogenesis of Ipomoea batatas in solid eultures and production of mature somatic embryos in liquid cultures for application to a bioreactor production system

Abstract: Somatic embryos of Ipomoea batatas Lam. (sweet potato cv. 'White Star') were produced in an airlift bioreactor. This work describes the optimization of the embryogenic system on semisolid medium, followed by transfer of the system to liquid cultures and ultimately to the airlift bioreactor. The physiological age of embryogenic callus influenced the number and overall morphology of the embryo population in both semisolid and liquid medium. Maximum mature embryo production (35 embryos 10 mg-~ inoculum) was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…This can be manifested in the study on Taxus chinensis cell culture which revealed that both cell growth and production of taxuyunnanine C (TC) increased with increase in concentration of ethylene in bubble column bioreactor (Pan et al, 2000). However, Burg (1973) observed that ethylene inhibited cell division, and this might suppress embryo elongation (Bieniek et al, 1995).…”
Section: Key Parameters For Efficient Bioreactor Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…This can be manifested in the study on Taxus chinensis cell culture which revealed that both cell growth and production of taxuyunnanine C (TC) increased with increase in concentration of ethylene in bubble column bioreactor (Pan et al, 2000). However, Burg (1973) observed that ethylene inhibited cell division, and this might suppress embryo elongation (Bieniek et al, 1995).…”
Section: Key Parameters For Efficient Bioreactor Systemsmentioning
confidence: 94%
“…For a well-functioning bioreactor, both the gas-liquid and liquid (medium)-solid (cells) mass transfers are important to conduct the respiration (metabolic process) of plant cells (Curtis, 2005). Carbon dioxide (CO 2 ), ethylene (C 2 H 4 ), ethanol (C 2 H 5 OH), and acetaldehyde (CH 3 CHO) are typically produced by respiring cultures (Thomas and Murashige, 1979;Perata and Alpi, 1991;Bieniek et al, 1995). Accumulation of these gases in the culture vessel inhibits growth of cultures (Jackson et al, 1985;Biddington and Robinson, 1991).…”
Section: Key Parameters For Efficient Bioreactor Systemsmentioning
confidence: 99%
“…The gas balance inside the bioreactor poses a challenge both in terms of obtaining a gas-balance permissible to somatic embryo development (Huang et al, 2006), as does managing the inhibitory shear stress from gas purging of the bioreactor (Bieniek et al, 1995). In our study, we have not studied the effect of the gas balance inside the flow cell.…”
mentioning
confidence: 94%
“…Plant regeneration through organogenesis has been shown in roses, Rosa hybrida, Rosa chinensis minima (Hsia and Korban, 1996); mulberry, Morus alba (Susheelamma et al , 1996); papaya, Carica papaya (Drew, 1992); date palm, Phoenix dactylifera (Tisserat, 1984); and taro, Colocasia esculenta (Sabapathy and Nair, 1995). Somatic embryogenesis has been demonstrated in vegetables such as Allium jistulosum L. (Kim and Soh, 1996); potato, Solanum tuberosum (Garcia and Martinez, 1995); sweet potato, Ipomoea batatas (Bieniek et al, 1995;Sonnino and Mini, 1993); omamentals, such as roses, Rosa hybrida and Rosa chinensis minima (Hsia and Korban, 1996); oleander, Nerium oleander L. (Santos et al , 1994); cyclamen, Cyclamen persicum (Kreuger et al, 1995); gladiolus, Gladiolus hort. (Stefaniak, 1994); and fmit trees, such as banana, Musa sp.…”
Section: Mutagenesis and Somatic Embryogenesismentioning
confidence: 98%